The Effect of ESG Score, Leverage, and Company Size on Company Value in the Financial Sector Listed on the IDX for the 2020–2024 Period - Rachma Nadhila Sudiyono; Ria Hartati; Thina Oktarina; Dwi Purwaningrum; Yunita Rahmawati (Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the effect of ESG Score, Leverage, and Firm Size on Firm Value in financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Firm value was measured using the Price to Book Value (PBV) ratio, leverage was measured using the Debt to Equity Ratio (DER), firm size was measured using the natural logarithm of total assets, and ESG Score was obtained from companies' sustainability reports. This study employed a quantitative approach with an associative method. The research population consisted of 45 financial sector companies, with a sample of 20 companies selected through purposive sampling, yielding 100 observation data. Secondary data in the form of annual financial reports and sustainability reports were obtained from www.idx.co.id. Panel data regression analysis was applied using EViews 9.0 software. Model selection results indicated that the Random Effect Model (REM) was the most appropriate model. The findings revealed that ESG Score, Leverage, and Firm Size had no significant effect on Firm Value, both partially and simultaneously. The coefficient of determination (R²) of 0.032833 indicated that only 3.28% of the variation in Firm Value was explained by ESG Score, Leverage, and Firm Size, while the remaining 96.72% was attributed to other factors not examined in this study.